USING CLOUD TECHNOLOGIES IN SOFTWARE VULNERABILITY ANALYSIS (Scientific journal of the Fergana State University, 2024)
Cloud technologies are playing an increasingly important role in the modern world of information technology, including software security. This study is aimed at examining the role of cloud technologies in software security and forecasting their further development.The study analyzes current trends in the use of cloud technologies to ensure software security, and also examines the prospects for the development of this area. Special attention is paid to the integration and automation of security in cloud environments, the use of artificial intelligence and machine learning, as well as the development of specialized cloud security solutions. It is predicted that in the future, cloud technologies will be increasingly in demand by companies and organizations, and will continue to evolve towards improving the flexibility, scalability and efficiency of software security.This research is valuable for information security specialists, IT department managers and all those interested in ensuring the security of information systems using cloud technologies.